Transparent reporting of multivariable prediction models in journal and conference abstracts: TRIPOD for abstracts - Heus, P; Reitsma, JB; Collins, GS; Damen, JAAG; Scholten, RJPM; Altman, DG; Moons, KGM; Hooft, L (American College of Physicians, 2020)
Clear and informative reporting in titles and abstracts is essential to help readers and reviewers identify potentially relevant studies and decide whether to read the full text. Although the TRIPOD (Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis) statement provides general recommendations for reporting titles and abstracts, more detailed guidance seems to be desirable. The authors present TRIPOD for Abstracts, a checklist and corresponding guidance for reporting prediction model studies in abstracts.